Diagnostic and Therapeutic Approach of Primary Spontaneous Pneumothorax in a Greyhound Dog - S. Saravanan; S. Kathirvel; G. Selvaraju (The Indian Veterinary Journal, 2024)
A two year old male Greyhound dog was presented with respiratory distress and hyporexia. Radiographic examination revealed accumulation of air in the thorax and elevated silhouette of the heart. Thoracocentesis was performed to stabilize the case by relieving the accumulated air in the thorax. The respiration rate and appetite returned to normal without any recurrence of the condition.